Selected Hiligayon Novels: Translation and Evaluation - Bacio Jr., Salvador P.; Cabiles, Neña Vanessa A; Cepeda, Ma. Ernalyn B.; Cordero, Evelyn M.; Denusta, Jonalyn L.; Embajador, Pearly Jade N.; Espedion Jr., Romeo T.; Quidato, Julie Gay B.; Diamante, Alexis L.; Ecube, Ma. Elfleda R.; Morga, Cynthia L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This descriptive-evaluative study aimed to translate and evaluate selected Hiligaynon novels. In the translation, the following steps were followed: reading and understanding the work to fully capture the general thought, essence, and message; translation and development of the first manuscript; validation and improvement of the first manuscript based on the suggestions of experts/consultants; revising, refining, and developing the final form and evaluating the appropriateness of the translated Hiligaynon novels. Three teachers of Hiligaynon literature and language evaluated the appropriateness of the translation. The result of the evaluation showed that the translated novels were appropriate as a whole, and also appropriate according to various criteria. It was concluded that the translators possess the characteristics and knowledge of the translated works, and also have proficiency in the two languages ​​involved in the translation. It is suggested to further polish the translation of selected Hiligaynon novels. Moreover, it is proposed to include the translated novels as teaching and reference materials for teachers, students, and researchers in schools and libraries and to carry out further translation of other Hiligaynon novels towards the development of local Ilonggo literature.